Changes in the Quality of Black Mulberry and Blueberry Sherbets During Storage - Ahsen Rayman Ergün; Yeliz Tekgül; Hamza Bozkır; taner baysal (Turkish Journal of Agriculture: Food Science and Technology)
This study was evaluated the quality properties of traditional drink sherbets that are prepared from black mulberry and blueberry fruits. After production sherbets were investigated to determine their pH, acidity, °brix and colour values, total sugar, phenolic, anthocyanin and antioxidant contents. Moreover the sherbets stored at 4°C during 2 months and the changes in these quality properties were examined per month. As a result statistically significant changes were observed in the quality properties of these sherbets of black mulberry and blueberry fruits which are known with their rich content of phytochemical compounds. The results show that in blueberry sherbet the degradation of phenolics was faster than black mulberry sherbet. Anthocyanins that are higher in black mulberry sherbets after production were preserved better in blueberry sherbets at the end of 2nd month. L*and a* values decreased for blackberry and blueberry sherbets during storage. b* value decreased from 5.59 to 4.92 for blackberry sherbet while it increased from 0.62 to 0.79 for blueberry sherbet at the end of the storage time.